Metaphors for God: The Characteristics of Metaphor and the Use of Metaphor in Contemporary Women's Preaching (Homiletic, 2011)
In academic writing, feminist theologians use various techniques for referring to God. For example, Rosemary R. Ruether uses the term "God/ess" and Elisabeth Schussler Fiorenza "G*d," but both of these written variations are problematic in verbal prayers, liturgies and sermons. In 1987, Sallie McFague explored metaphor as an appropriate method for speaking about God. This article explores seven characteristics of metaphor based on the work of Sallie McFague, Sandra Schneiders and Ruth Duck. This article then briefly details the results and implications of a survey of women's sermons, read in light of the seven characteristics of metaphor.